Endobronchial ultrasound-guided lymph node biopsy with transbronchial needle forceps: a pilot study - Herth, Felix; Gompelmann, Daniela; Kahn, Nicolas; Schuhmann, Maren; Eberhardt, Ralf (The European respiratory journal, 2012)
One limitation of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is the size of the available needles, frequently yielding only cells for cytological examination. The aim of this pilot study was to evaluate the efficacy and safety of newly developed needle forceps to obtain tissue for the histological diagnosis of enlarged mediastinal lymph nodes. Patients with enlarged, positron emission tomography (PET)-positive lymph nodes were included. The transbronchial needle forceps (TBNF), a sampling instrument combining the characteristics of a needle (bevelled tip for penetrating through the bronchial wall) with forceps (two serrated jaws for grasping tissue) was used through the working channel of the EBUS-TBNA scope. Efficacy and safety was assessed. 50 patients (36 males and 14 females; mean age 51 yrs) with enlarged or PET-positive lymph nodes were included in this pilot study. In 48 (96%) patients penetration of the bronchial wall was possible and in 45 patients tissue for histological diagnosis was obtained. In three patients TBNF provided inadequate material. For patients in whom the material was adequate for a histological examination, a specific diagnosis was established in 43 (86%) out of 50 patients (nonsmall cell lung cancer: n=24; small cell lung cancer: n=7; sarcoidosis: n=4; Hodgkin's lymphoma: n=4; tuberculosis: n=2; and non-Hodgkin’s lymphoma: n=2).No clinically significant procedure-related complications were encountered. This study demonstrated that EBUS-TBNF is a safe procedure and provides diagnostic histological specimens of mediastinal lymph nodes.